Stimulasi Kognitif Melalui Media Permainan Manipulatif Pada Anak Usia Dini - Hikrawati; Rahmatia; Nurul Asqia (Kilau Publishing, 2025)
The purpose of this study was to determine how cognitive stimulation through the use of manipulative play media in early childhood. Early childhood is a period where growth and development are developing rapidly, one of which is in the Cognitive aspect which consists of the ability to think, understand, solve problems, and make decisions. The study was conducted with a descriptive qualitative approach to children in group B at Nurul Hidayah Lempangan Kindergarten. Data analysis techniques in this study consisted of observation, interviews, documentation and document review. The results of the study showed that children were very interested in manipulative play media, marked by a significant increase in cognitive abilities, such as shapes, arranging patterns, solving simple problems, as well as memory and concentration. This study confirms that manipulative play, when applied with the right strategy and accompanied by teachers or parents, can be a fun and effective learning tool to support cognitive development.